Stroke Hemoragik dengan Riwayat Hipertensi Tidak Terkontrol: Sebuah Laporan Kasus - Aisyah, Putri; Putri , Pratiwi Hendro; Pangestu, K Widhi Indra; Salsabila, Salsabila; Rahma, Balqist Ar; Putri, Siti Fhatima Novariani (CV. Jasa Sukses Abadi, 2024)
Stroke is a functional disorder of the brain that occurs suddenly with clinical signs and symptoms, both focal and global, that last more than 24 hours, or can cause death, caused by impaired cerebral blood circulation. Hemorrhagic stroke is a rupture of a brain blood vessel causing blood to leak into the brain parenchymal tissue, cerebrospinal fluid space around the brain or a combination of both. A 62 year old man came to the emergency room at Jendral Ahmad Yani Metro Hospital accompanied by his family with complaints of sudden loss of consciousness since 3 hours ago. Previously, the patient complained of severe, sudden headaches, which did not decrease at rest or after taking headache medication, vomited twice, vomited without nausea, and finally the patient fainted. Vomiting contains liquid with food. The patient has a history of uncontrolled hypertension since 10 years ago. Brain pons bleeding was found with an estimated bleeding volume of +1.75 ml, but the family refused surgery. The patient's general condition continued to decline so that after 3 days of treatment in the ward of the Department of Neurology, the patient was declared dead.